2022
DOI: 10.1021/acs.joc.1c03085
|View full text |Cite
|
Sign up to set email alerts
|

Total Asymmetric Synthesis and Stereochemical Confirmation of (+)- and (−)-Lyoniresinol and Its Deuterated Analogues

Abstract: Lyoniresinol and its derivatives are lignans which have been isolated from a plethora of plant species. In addition to exhibiting a range of interesting biological activities including anticancer, anti-inflammatory, antimicrobial, and others, these compounds have also been discovered in wines and spirits and shown to have gustatory effects in these alcoholic matrices. (+)-Lyoniresinol 1 is reported to impart a strong bitter taste while its enantiomer (−)-lyoniresnol 2 is tasteless. The first total asymmetric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It should be noted that our approach of using aldol addition of a substituted benzaldehyde, followed by deoxygenation, rather direct alkylation of a benzylic halides was preferred due to the prior experiences of ourselves, and others, who have shown that direct alkylation of a highly electron-rich benzylic halides to be highly problematic and inconsistent. 21,22 Following this retrosynthetic plan, we herein report the synthesis of 1-3 for the first time and in addition, five unnatural lignan derivatives were also accessed using the same strategy by altering the aromatic substitutions with common lignan patterns.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that our approach of using aldol addition of a substituted benzaldehyde, followed by deoxygenation, rather direct alkylation of a benzylic halides was preferred due to the prior experiences of ourselves, and others, who have shown that direct alkylation of a highly electron-rich benzylic halides to be highly problematic and inconsistent. 21,22 Following this retrosynthetic plan, we herein report the synthesis of 1-3 for the first time and in addition, five unnatural lignan derivatives were also accessed using the same strategy by altering the aromatic substitutions with common lignan patterns.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…It should be noted that our approach of using aldol addition of a substituted benzaldehyde, followed by deoxygenation, rather direct alkylation of a benzylic halides was preferred due to the prior experiences of ourselves, and others, who have shown that direct alkylation of a highly electron-rich benzylic halides to be highly problematic and inconsistent. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…The aldehyde functionality in vitexin 1 was envisaged to be accessed through selective oxidation of an allylic alcohol. This oxidation could therefore take place from the diol product accessed through reductive cleavage of dihydro-naphthalene lactone 1 . , Lactone 1 was proposed to be formed via acid-catalyzed cyclization of butyrolactone 2 , with subsequent elimination of the C7′ substituent to install the allylic system. This was envisaged to be possible by using an acid-labile protecting group at C7′.…”
mentioning
confidence: 99%
“…yield from 4-pentenoic acid and ( S )-4-benzyl-2-oxazolidinone . Initially, isopropyl protected vanillin was chosen as the aldol partner and underwent an anti -aldol addition , to give an 83% yield of aldol 5a with excellent diastereomeric excess ( e.e . > 99%), determined by 1 H NMR (Scheme ).…”
mentioning
confidence: 99%
See 1 more Smart Citation